Combined effect of resting heart rate and physical activity on ischaemic heart disease: mortality follow-up in a population study (the HUNT study, Norway). Issue 2 (7th January 2010) - Nauman, J; Nilsen, T Ivar Lund; Wisløff, U; Vatten, L J
Abstract : Background: The combined effect of resting heart rate (RHR) and physical activity (PA) on ischaemic heart disease (IHD) has never been assessed. The objective of this study was to assess the association of RHR with IHD mortality, and to evaluate the potentially modifying effect of PA on this association. Methods: In a prospective cohort study of 24 999 men and 25 089 women free from cardiovascular disease at baseline, Cox proportional hazard models were used to estimate adjusted hazard ratios of death from IHD related to RHR measured at baseline. The combined effect of RHR and self-reported PA on the risk of death from IHD was also assessed. Results: During a mean of 18.2 (SD 4) years of follow-up, 2566 men and 1814 women died from cardiovascular causes. For each increment of 10 heart beats per minute, risk of death from IHD was 18% higher in women <70 years of age (p<0.001); no such association was observed among women ≥70 years. Among men, there was a corresponding 10% higher risk in the younger (p = 0.004), and 11% higher risk in the older age group (p = 0.01). Among women, the risk associated with high RHR was substantially attenuated in those who reported a high level of PA, whereas in men, there was no clear indication that PA could modify the positive effect of RHR. Conclusion: RHR is positively associated with the risk of death from IHD, and among women, the results suggest that by engaging in PA, the risk associated with a high RHR may be substantially reduced.